Glabratephrin reverses doxorubicin resistance in triple negative breast cancer by inhibiting P-glycoprotein. (January 2022) - Abd-ellatef, Gamal Eldein Fathy; Gazzano, Elena; El-Desoky, Ahmed H.; Hamed, Ahmed R.; Kopecka, Joanna; Belisario, Dimas Carolina; Costamagna, Costanzo; S. Marie, Mohamed Assem; Fahmy, Sohair R.; Abdel-Hamid, Abdel-Hamid Z.; Riganti, Chiara
Abstract: Triple-negative breast cancer is one of the most aggressive breast cancer. The first therapeutic option is chemotherapy, often based on anthracycline as doxorubicin. However, chemotherapy efficacy is limited in by the presence of P-glycoprotein (Pgp), a membrane transporter protein that effluxes doxorubicin, reducing its cellular accumulation and toxicity. Inhibiting Pgp activity with effective and non-toxic products is still an open challenge. In this work, we demonstrated that the natural product Glabratephrin (Glab), a prenylated flavonoid from Tephrosia purpurea with a unique chemical structure, increased doxorubicin accumulation and cytotoxicity in triple negative breast cancer cells with high levels of Pgp, characterized by both acquired or intrinsic resistance to doxorubicin. Glab also reduced the growth of Pgp-expressing tumors, without adding significant extra-toxicities to doxorubicin treatment. Interestingly, Glab did not change the expression of Pgp, but it reduced the affinity for Pgp and the efflux of doxorubicin, as suggested by the increased Km and the reduced Vmax. In silico molecular docking predicted that Glab binds two residues (phenylalanine 322, glutamine 721) localized in the transmembrane domains of Pgp, facing the extracellular environment. Moreover, site-directed mutagenesis identified glycine 185 as a critical residue mediating the reduced catalytic efficacy of Pgp elicited by Glab. We propose Glab as an effective and safe compound able to reverse doxorubicin resistance mediated by Pgp in triple negative breast cancers, opening the way to a new combinatorial approach that may improve chemotherapy efficacy in the most refractory and aggressive breast cancer. Graphical Abstract: ga1 Highlights: Glabratephrin is a natural prenylated flavonoid from Tephrosia purpurea. Glabratephrin reverses resistance to doxorubicin in triple negative breast cancer. Glabratephrin binds P-glycoprotein and reduces its catalytic activity. Glabratephrin is effective and safe in triple negative breast cancer xenografts.